2020
DOI: 10.1002/app.49291
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of pineapple peel waste and sisal fiber: Study of cellulose nanocrystals on polypropylene nanocomposites

Abstract: The present study focuses on the isolation and characterization of the cellulose nanocrystals (CNCs) from the pineapple peel waste (PPW) (agro‐waste) and sisal fiber (SiF) (natural fiber) employing the acid hydrolysis method, and its comparison with the commercially available CNCs (CNC‐C). Furthermore, the CNCs from PPW, SiF, and CNC‐C were subjected to transmission electron microscopy (TEM), Fourier transform electron microscopy, X‐ray diffraction, particle size distribution, and zeta potential analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…The results are consistent with Mehanny, et al [22]; nanocellulose obtained from palm wastes via 20% H2SO4 (v/v) at 120 °C for 30 min was reported in spherical particles of 42-82 nm diameter. However, the morphology of isolated CN was different from some previous studies, as they were rod-like or needle-shaped [11,23,24]. Yang, et al [25], sus- The results are consistent with Mehanny, et al [22]; nanocellulose obtained from palm wastes via 20% H 2 SO 4 (v/v) at 120 • C for 30 min was reported in spherical particles of 42-82 nm diameter.…”
Section: Morphology and Yield Analysissupporting
confidence: 79%
See 1 more Smart Citation
“…The results are consistent with Mehanny, et al [22]; nanocellulose obtained from palm wastes via 20% H2SO4 (v/v) at 120 °C for 30 min was reported in spherical particles of 42-82 nm diameter. However, the morphology of isolated CN was different from some previous studies, as they were rod-like or needle-shaped [11,23,24]. Yang, et al [25], sus- The results are consistent with Mehanny, et al [22]; nanocellulose obtained from palm wastes via 20% H 2 SO 4 (v/v) at 120 • C for 30 min was reported in spherical particles of 42-82 nm diameter.…”
Section: Morphology and Yield Analysissupporting
confidence: 79%
“…Yang, et al [25], sus- The results are consistent with Mehanny, et al [22]; nanocellulose obtained from palm wastes via 20% H 2 SO 4 (v/v) at 120 • C for 30 min was reported in spherical particles of 42-82 nm diameter. However, the morphology of isolated CN was different from some previous studies, as they were rod-like or needle-shaped [11,23,24]. Yang, et al [25], suspected that the resulting sphere shape of CN could be because of pretreatment processes such as milling, fiber regeneration prior to acid hydrolysis, and TEMPO-assisted oxidation.…”
Section: Morphology and Yield Analysismentioning
confidence: 85%
“…The biomass generated in pineapple production has been used mainly to extract cellulose nanocrystals. The CNC obtained are by acid hydrolysis and it has been reported that they are extracted from different parts of the pineapple plant such as the crown [22,23], the stem [3], the peel [24] and the leaves [25,26]. Due to the cellulosic availability in pineapple plant, it is important to explore the possibility of producing CNF from this raw material.…”
Section: Introductionmentioning
confidence: 99%
“…This difference will influence the final application given the new material. For example, CNC are shorter and smaller and have better resistance properties and greater crystallinity than cellulose nanofibers and can be used as reinforcement materials [24]. Cellulose nanofibers can crosslink and form high strength nanostructures for other applications [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, the isotactic polypropylene (iPP) has been found to have many applications in various areas in view of its satisfactory properties and relative low material cost [1][2][3]. The discovery of stereospecific olefins polymerization catalysts enabled the efficient iPP synthesis on the industrial scale and its widespread use in man-made material technology, especially in the production of composites [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%